Alteration of time-resolved autofluorescence properties of rat aorta, induced by diabetes mellitus. (6th September 2016) - Uherek, M; Uličná, O; Vančová, O; Muchová, J; Ďuračková, Z; Šikurová, L; Chorvát, D
Abstract: Changes in autofluorescence properties of isolated rat aorta, induced by diabetes mellitus, were detected using time-resolved fluorescence spectroscopy with pulsed ultraviolet (UV) laser excitation. We demonstrated that time-resolved spectroscopy was able to detect changes in aorta tissues related to diabetes and unambiguously discriminate diabetic ( τ 1 0.63 ± 0.05 ns, τ 2 3.66 ± 0.10 ns) samples from the control ( τ 1 0.76 ± 0.03 ns, τ 2 4.48 ± 0.15 ns) group. We also report changes in the ratio of relative amplitudes of the two lifetime component in aorta tissue during diabetes, most likely related to the pseudohypoxic state with altered NADH homeostasis.